2023
DOI: 10.3390/rs15194664
|View full text |Cite
|
Sign up to set email alerts
|

High-Precision GPU-Accelerated Simulation Algorithm for Targets under Non-Uniform Cluttered Backgrounds

Yongqiang Zhang,
Jianxiong Zhou,
Zhiyong Song
et al.

Abstract: This article presents a high-precision airborne video synthetic aperture radar (SAR) raw echo simulation method aimed at addressing the issue of simulation accuracy in video SAR image generation. The proposed method employs separate techniques for simulating targets and ground clutter, utilizing pre-existing SAR images for clutter simulation and employing the shooting and bouncing rays (SBR) approach to generate target echoes. Additionally, the method accounts for target-generated shadows to enhance the realis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The high integration of ViSAR real-time imaging processing components also puts higher demands on the computing power of hardware platforms. Currently, the research on onboard real-time processing mainly involves three commonly used platforms, i.e., digital signal processing (DSP) [17], graphic processing unit (GPU) [18][19][20], and FPGA [21][22][23][24][25]. In 2022, Wang et al reported a terahertz SAR imaging processing system based on a multi-core DSP.…”
Section: Introductionmentioning
confidence: 99%
“…The high integration of ViSAR real-time imaging processing components also puts higher demands on the computing power of hardware platforms. Currently, the research on onboard real-time processing mainly involves three commonly used platforms, i.e., digital signal processing (DSP) [17], graphic processing unit (GPU) [18][19][20], and FPGA [21][22][23][24][25]. In 2022, Wang et al reported a terahertz SAR imaging processing system based on a multi-core DSP.…”
Section: Introductionmentioning
confidence: 99%